2009
DOI: 10.1158/1535-7163.mct-08-1208
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical evaluation of a novel pyrimidopyrimidine for the prevention of nucleoside and nucleobase reversal of antifolate cytotoxicity

Abstract: Antifolates have been used to treat cancer for the last 50 years and remain the mainstay of many therapeutic regimes. Nucleoside salvage, which depends on plasma membrane transport, can compromise the activity of antifolates. The cardiovascular drug dipyridamole inhibits nucleoside transport and enhances antifolate cytotoxicity in vitro, but its clinical activity is compromised by binding to the plasma protein α 1 -acid glycoprotein (AGP). We report the development of a novel pyrimidopyrimidine analogue of dip… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 21 publications
(17 reference statements)
0
14
0
Order By: Relevance
“…Notwithstanding solubility problems with diaryl carbamates ( 13 , 15 , 17 , 19 ), it was evident that the monoaryl carbamates ( 12 , 16 , 18 ) retained NT-inhibitory activity at least comparable with 6 , 20 , and 21 , whereas the corresponding diaryl carbamates ( 13 , 17 , 19 ) were weakly active ( 13 ) or inactive ( 17 , 19 ) where evaluation was possible (Figure A). Crucially, the desired lack of significant AGP binding in vitro for NU3108 ( 6 ) was also observed for the monoglycine carbamate ( 20 ) and the monoaryl carbamates 12 , 16 , and 18 , with no reduction in potency being evident in the presence of physiologically relevant concentrations (5 mg/mL) of AGP (Figure B) . By contrast, the NT-inhibitory activity of 3 was reduced by approximately 66% under these conditions.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Notwithstanding solubility problems with diaryl carbamates ( 13 , 15 , 17 , 19 ), it was evident that the monoaryl carbamates ( 12 , 16 , 18 ) retained NT-inhibitory activity at least comparable with 6 , 20 , and 21 , whereas the corresponding diaryl carbamates ( 13 , 17 , 19 ) were weakly active ( 13 ) or inactive ( 17 , 19 ) where evaluation was possible (Figure A). Crucially, the desired lack of significant AGP binding in vitro for NU3108 ( 6 ) was also observed for the monoglycine carbamate ( 20 ) and the monoaryl carbamates 12 , 16 , and 18 , with no reduction in potency being evident in the presence of physiologically relevant concentrations (5 mg/mL) of AGP (Figure B) . By contrast, the NT-inhibitory activity of 3 was reduced by approximately 66% under these conditions.…”
Section: Resultsmentioning
confidence: 76%
“…While the 3 H-TdR transport assay served as a useful initial screen, a 3 H-TdR incorporation assay, employing the COR-L23 human lung carcinoma tumor cell line, was used for subsequent studies with selected compounds, as this assay provides a more representative value for NT inhibition . As expected, the parent pyrimidopyrimidine 6 (IC 50 = 26 ± 5 nM) exhibited activity comparable with 3 (IC 50 = 15 ± 4 nM), with 6 and the homochiral derivative 11 proving equipotent.…”
Section: Resultsmentioning
confidence: 84%
“…However, it appeared that the prodrug did not have very strong and sustained in vivo inhibition which is required to drastically reduce the viral load. It was suggested that the prodrug should possess a much higher potency (at least twofold greater) to have an equivalent effect to that of the pyrimidopyrimidine derivative of dipyridamole (Thomas et al 2009). …”
Section: Dipyridamole Moiety-based Prodrugmentioning
confidence: 99%
“…Isoxazolo[5,4‐ d ]pyrimidinones and pyrazolo[3,4‐ d ]pyrimidinones are potent anticancer agents . Pyrimido[4,5‐ d ]pyrimidinones display significant antitumor, anti‐inflammatory, and antimicrobial activities, prevention of nucleoside and nucleobase reversal of antifolate cytotoxicity and the inhibition of cellular proliferation in breast cancer . According to the above‐mentioned findings and in the persistence of our strategies for the synthesis of novel bioactive heterocycles, we report here the synthesis of some heterocycles fused with pyrimidinone ring with the objective of evaluating their cytotoxicity and bleomycin‐dependent DNA damage activities.…”
Section: Introductionmentioning
confidence: 99%